Choosing A Competence, Education And Work Discipline On The Productivity Of Food Security And Agricultural Services For The Future - Heni Rochaeni; Ellin Herlina; Mahfud (PT. Berkah Digital Teknologi, 2022)
Purpose of the study — find out whether competence, Education, and work discipline affect work productivity either partially or simultaneously.Research method— Causal associative research with a quantitative approach using a questionnaire survey method. The population in the study was the staff of the Food and Agriculture Security Service